New synthetic route for 1,2-diketo compounds using unexpected C-C bond cleavage by PCC - Bhosale, Shrikar M.; Momin, Aadil A.; Gawade, Rupesh L.; Puranik, Vedavati G.; Kusurkar, Radhika S. (Tetrahedron Letters, 2012)
An efficient method has been established for the preparation of 1,2-diketones by unexpected C-C bond cleavage in 4-keto-2-hydroxy esters using pyridiniumchlorochromate (PCC). (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: 1; 2-Diketones; C-C bond cleavage; PCC